Sistem Notifikasi Monitoring Server Pada BOT Telegram Menggunakan Cronjob Berbasis Web (Studi Kasus : PT. Ekanuri Group) - Ahmad Juantoro; Niki Ratama (CV. Multi Kreasi Media, 2022)
Server monitoring is an activity carried out to monitor or monitor a running server and allows detecting a problem on the server. Generally, this monitoring requires someone to always be in the server room to find out how things are and conditions on the server. At this time the IT Division at PT. Ekanuri Group monitors the Server by pinging the IP/Domain Server or remotely the server and ensuring the server is alive, apart from the many other IT Division work that must be completed, it is not possible to always monitor regularly. Telegram is a chat messaging application that allows its users to send end-to-end encrypted chat messages for added security. Telegram is a cloud-based application that makes it easy for users to move conversations between smartphones, tablets, web and desktops. It is hoped that the results of this research will be in the form of a system that monitors servers regularly, if the registered server cannot be accessed within three minutes, the system will send a Telegram message to the IT Division to inform whether the server is in an up/down state.